2018
DOI: 10.1111/jgh.14289
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and survival of esophageal cancer in Korea: Analysis of the Korea Central Cancer Registry Database

Abstract: Background and Aim: The diagnostic and therapeutic modalities of esophageal cancer have recently improved in Asia, and its prognosis is expected to change. This study provides a population-based report on the epidemiology of esophageal cancer in Korea. Methods: Cancer incidence data from 1999 to 2013 were obtained from the Korea Central Cancer Registry, covering the entire population. Age-standardized incidence rates and annual percent changes were calculated according to subsites and histological types. Fivey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 29 publications
2
41
1
1
Order By: Relevance
“…Third, all included patients were men who were diagnosed with squamous cell carcinoma. Although the majority of esophageal cancer patients in Korea are men with squamous cell carcinoma [56], further studies that include women and various histologic types of esophageal cancer are needed. Finally, because there is no definite consensus on the cut-off value of SMI for defining sarcopenia, this study adopted the value proposed by a previous population-based study [27], which was used in several recent studies on cancer patients [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Third, all included patients were men who were diagnosed with squamous cell carcinoma. Although the majority of esophageal cancer patients in Korea are men with squamous cell carcinoma [56], further studies that include women and various histologic types of esophageal cancer are needed. Finally, because there is no definite consensus on the cut-off value of SMI for defining sarcopenia, this study adopted the value proposed by a previous population-based study [27], which was used in several recent studies on cancer patients [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinomas are more commonly distributed in upper and middle thirds of esophagus; while adenocarcinomas are more common in distal esophagus and associated with gastroesophageal reflux disorder and Barrett's esophagus [26,27]. Shin et al [28] reported that, in Korea, squamous cell carcinoma was the most common histological type (90.2%) of all esophageal cancer in 2013, followed by adenocarcinoma (3.1%). In our study, two patients had esophageal cancer with severe dilatation in upper esophagus as seen on chest X-ray imaging, histologically confirmed as squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of esophageal cancer ranked fifth in China and third in rural areas globally, after lung cancer and gastric cancer, 7 indicating the heavy burden of this cancer. 1 The mortality rate of cancer, especially gastrointestinal cancer, is on the decline in countries where living standards have continuously improved, such as United States, [8][9][10] Switzerland, Denmark, Finland, [11][12][13][14] Korea, 15 and China. 16 The results of the third retrospective survey on the causes of death in China showed that the mortality rate of esophageal cancer decreased by 33.6% from the first survey and by 41.6% from the second survey.…”
Section: Discussionmentioning
confidence: 99%